Biodegradation of Reactive Orange 16 Dye in Microbial Fuel Cell: An Innovative Way to Minimize Waste Along with Electricity Production - Shahi A.; Rai B.N.; Singh R.S. (My University, 2025)
Microbial fuel cell (MFC) is an attractive green technology which harnesses the power of microorganism for the production of electricity along with bioremediation of waste. However, the bioremediation of the high concentration of dye wastewater in MFC remains unclear. In present study, double-chambered MFC inoculated with mixed bacterial consortium was used for bioremediation of reactive orange 16 (RO-16) dyes at a very high and variable concentration range of 100 to 1000 ppm. Maximum voltage was obtained for 100 ppm of dye and was found to be 0.5791 V along with a power density of 0.0851 W/m3. Till 500 ppm concentration of dye COD removal efficiency remains in range of 40 to 100% thereafter it decreases. The maximum concentration of CO2 was found to be 2% at 1000 ppm which confirms the biodegradation phenomena in MFC. Kinetics of biodegradation of reactive orange 16 were studied using Haldane inhibitory kinetic model and kinetic constants μmax, Ks, and Ki were calculated and found to be 0.417 day−1, 206.2 ppm, and 447.12 ppm respectively. The experimental results showed inhibitory condition in the MFC after 500 ppm and it was supported by the value of inhibitory kinetic constant Ki = 447.12 ppm. This study opened the possibility of bioremediation of dyes at high concentrations in MFCs. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.